Comparing the moral intelligence from Imam Ali’s viewpoint with theory of Borba - Saeid Shabanloo, Karim; Behroozi, Nasser; Shehniyailagh, Manizheh; Safaei Moghaddam, Masoud (Opción, 2019)
This study aimed to present the moral intelligence theory from the viewpoint of Imam Ali. The methodology of this study is qualitative with the grounded theory method. As a result, according to the moral intelligence theory of Imam Ali, moral intelligence encompasses three divine, intrapersonal and extra-personal domains. In conclusion, it seems that Imam Ali’s orders provide a holistic view of moral intelligence; hence, moral intelligence can be taught paying attention to the culture of Islamic society and providing an organized educational program based on the relevant findings